2017
DOI: 10.4209/aaqr.2016.08.0374
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation of Ground Level Ozone Concentrations and its Health Impacts in an Urban Area in India

Abstract: The present study was designed to analyze the spatial distributions of ground-level ozone (GLO) concentrations in Ranchi (Jharkhand, India) using geostatistical approaches. From September 2014 to August 2015, monthly GLO concentrations were monitored in 40-identified locations distributed in the region of study. In every month, the monitoring was done at three different time periods of the day; 5.30 AM to 7.30 AM, 11.30 AM to 1.30 PM, and 5.30 PM to 8 PM). The time duration was assigned based on the temporal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…These results are consistent with the research of Gorai et al [69], who found that temporal changes in tropospheric ozone concentrations clearly indicate a general 24-h cycle, with the maximum concentration noted from late morning to mid-afternoon and the minimum during the night and in the early morning. This corresponds to the daily course of air temperature.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the research of Gorai et al [69], who found that temporal changes in tropospheric ozone concentrations clearly indicate a general 24-h cycle, with the maximum concentration noted from late morning to mid-afternoon and the minimum during the night and in the early morning. This corresponds to the daily course of air temperature.…”
Section: Resultssupporting
confidence: 93%
“…The The results of the study are in agreement with those reported by Parrish et al [67], who found higher levels of tropospheric ozone in spring and summer than in autumn and winter. The effect of climatic conditions on O 3 concentrations is widely discussed in the literature [67][68][69][70]. According to De Nevers [71], Paudsainee et al [72], Khoder [73], and Langner et al [74], the intensive solar radiation, high temperature, and high relative humidity in summer contribute to high O 3 concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Urban air pollution is a major ecological threat in most developing countries (Gorai et al, 2017). The consistent rise in greenhouse gas emissions is also intensifying and therefore affects the earth's climate system (Nsubuga et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During CCT, NO 2 was used up for the O 3 formation. CCP occurred when photochemical reaction rate started to surpass NO x titration rate and it was represented by the interception point between O 3 and NO 2 concentration on the plot [10], [11], [19]- [21]. The O 3 uni-modal peaks usually after CCT approximately between 12.00 p.m. to 4.00 p.m.…”
Section: B Diurnal Variationsmentioning
confidence: 99%